Spermidine-Binding Proteins. Purification and Expression Analysis in Maize - Tassoni, Annalisa (American Society of Plant Physiologists, 2002)
Polyamine-binding proteins have been identified in a wide range of organisms, including mammals, yeasts, and bacteria. In this work, we have investigated specific spermidine binding to plant membrane proteins purified from microsomes of etiolated maize (Zea mays) coleoptiles. In the final purification step, specific spermidine-binding activity (K(d) 6.02 10(−7) m) was eluted from a HiTrapQ fast-protein liquid chromatography column at about 0.25 m NaCl, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the most active fraction showed a major polypeptide of about 60 kD and another copurifying 18-kD protein. Competition experiments, performed on HiTrapQ active fractions, confirmed the specificity of the binding. Upon Sephadex G-100 gel filtration, spermidine binding was associated almost exclusively with the 18-kD protein. On the basis of the N-terminal sequences, degenerate oligonucleotide probes were designed and used to isolate, by reverse transcriptase-polymerase chain reaction and polymerase chain reaction, cDNA fragments of about 1 kb for the 60-kD protein, and 0.9 kb for the 18-kD protein. Northern-blot analysis performed on etiolated coleoptiles and different tissues from 10-d-old maize plants indicated the presence of two different mRNAs of 1.7 and 0.7 kb. Southern-blot analysis indicated that the genes encoding the 60- and 18-kD proteins are probably derived from differential processing of the same precursor mRNA. Using rabbit polyclonal antibodies raised against these proteins, affinity purification and dot-blot experiments detected analogous membrane proteins in monocot and dicot plants.